Copper(I)-catalyzed stereoselective hydrogenation of 1, 3-diynes and enynes. Issue 33 (17th August 2017) - Thiel, Niklas O.; Kemper, Sebastian; Teichert, Johannes F.
Abstract: A stereoselective hydrogenation of 1, 3-diynes with an air-stable copper(I)/N-heterocyclic carbene complex, [IPrCuOH], has been developed. The corresponding products, 1, 3-dienes, are obtained in a stereoselective manner depending on their substitution pattern: Diaryl-diynes yield E, E -1, 3-dienes, whereas dialkyl-diynes are converted to the corresponding Z, Z -1, 3-dienes. Hydrogenation and deuteration experiments with enynes indicate that these are competent reaction intermediates in the hydrogenation of diynes. Graphical abstract: